On Surface Grind Hardening Induced Residual Stresses - Salonitis, Konstantinos (Elsevier, 2014)
Grind hardening process utilizes the heat generated in the grinding area for the surface heat treatment of the workpiece. The workpiece surface is heated above the austenitizing temperature by using large values of depth of cut and low workpiece feed speeds. The workpiece undergoes martensitic phase transformation increasing its hardness in the surface layer. Usually compressive residual stresses are induced in the surface layer. In the present paper, modeling and prediction of the residual stresses profile as a function of the process parameters is presented. The model's results are validated for two cases; a dry grind hardening and a coolant assisted grind hardening of AISI 1045 steel.
Keywords: Residual stresses; Finite element method; grinding; grind-hardening